The effect of digitalization on service production in Finnish municipalities - Partanen, Sirpa (2022)
Digitalization is a current phenomenon both in Finland and globally. It modifies existing practices and creates entirely new ones in both private and public sector. The development of digital technologies provides new opportunities for organizations to enhance their operations and business models. At the same time, the share of services in the employment and production structure of societies has increased and the shift from product-oriented society to the service economy has been inevitable. As a result of this societal transformation, the customer experience and shared value creation have become key strategic factors for organizations. The emphasis on customer experience has brought Service Design methods into service development. Service Design is user-centered and participatory development and design of services using traditional design methods. Comprehensiveness, visuality and interdisciplinary are characteristic for Service Design. Additionally, it is often experimental, iterative, and agile design of services. The primary purpose of Service Design is to create a service which meets both the needs of the users and the business objectives of the service provider. Using Service Design methods organizations can identify the essential services for business. These can be existing services that require development or quite new services. Master’s thesis literature review explored digital transformation as a social phenomenon and digitalization from the perspective of organizations. In addition, the literature review examined the service-dominant logic and Service Design process and principles. Since in the scientific research digitalization has been studied mostly from the business perspective, the master’s thesis focuses on examining digitalization from the perspective of the public sector, especially Finnish municipalities. In the empirical part of the master’s thesis, both the effects of digitalization on municipal operation and the application of Service Design methods in the development of digital services were investigated by interviewing persons responsible for digital services. The results of the study indicate the changes in the operating environment force the municipalities to provide digital services, but on the other hand, digitalization creates opportunities to improve operational efficiency, save costs and above all, serve the residents better.